Primary follicular lymphoma of the testis in childhood: an entity with peculiar clinical and molecular characteristics. Issue 9 (1st September 2002) - Pileri, S A; Sabattini, E; Rosito, P; Zinzani, P L; Ascani, S; Fraternali-Orcioni, G; Gamberi, B; Piccioli, M; Vivenza, D; Falini, B; Gaidano, G
Abstract : Background/Aims: Paediatric primary follicular lymphoma of the testis (PPFLT) is exceptional: the few reported cases seem to lack BCL-2 gene rearrangement and/or protein expression. The aim of this study was to characterise a PPFLT arising in a 4 year old boy. Methods: This case was characterised using conventional histological analysis, immunohistochemistry, and a polymerase chain reaction based method for the detection of immunoglobulin VH chain rearrangements. Results: The neoplasm was staged I E /A; left orchiectomy and chemotherapy were performed, producing complete remission. Histology showed a predominantly follicular lymphoid infiltrate mainly composed of centroblast-like cells. The phenotype was CD20 +, CD79a +, CD10 +, bcl-6 +, B cell specific activating protein +, κ light chain +, CD30 −/+, interferon regulating factor 4 −/+, c-myc −/+, λ light chain −, CD3 −, bcl-2 −, p53 −, cytokeratin −, and placental alkaline phosphatase − . Lymphomatous elements were found within a CD21 + follicular dendritic cell network and 70% were positive for Ki-67/MIB-1. Molecular analysis revealed monoclonal immunoglobulin heavy chain gene rearrangement and BCL-6 mutations, in the absence of BCL-2 major breakpoint and BCL-2 minor cluster region rearrangements, p53 mutations, and death associated protein kinase gene hypermethylation. Conclusions: These findings suggest a different pathogenesis of PPTFL compared with adult follicular lymphoma and might explain its favourable course in spite of aggressive histology.